Genomic and immune heterogeneity are associated with differential responses to therapy in melanoma - Alexandre Reuben (Nature Portfolio, 2017)
Melanoma: Tumor differences within a patient may explain heterogeneous responses Patients with metastatic melanoma display molecular and immune differences across tumor sites associated with differential drug responses. A team led by Jennifer Wargo from the University of Texas MD Anderson Cancer Center, Houston, USA, studied the radiological responses of 60 patients with metastatic melanoma, half of whom received targeted drug therapy and half of whom received an immune checkpoint inhibitor. The majority (83%) showed differences in responses across metastases. The group then profiled tumors in a subset, and found molecular and immune heterogeneity in different tumors within the same patient. Heterogeneity in mutational and immune profiles within tumors from individual patients could explain differences in treatment response. Knowing this, the authors emphasize the importance of acquiring biopsies from more than one tumor site in order to best tailor therapies to the features of metastatic cancer.